DAMPAK "THE LODGE" SEBAGAI DESTINASI WISATA TERHADAP PERUBAHAN SOSIAL EKONOMI MASYARAKAT DESA CIBODAS LEMBANG - Lifia Dwi Triastiany, - (2020)
The aim of this research is to see the community's response and the socio-economic impacts from the existence of The Lodge tourism destination for the people of Cibodas Lembang Village. The method used in this research is descriptive quantitative one variable with data collection techniques are documentation, semi-structured interviews, and questionnaires. There are 19 items tested in the questionnaire. The people of Cibodas Village are the participants in this research. There are 97 participants obtained using the Slovin formula, where the sampling technique used is random sampling. The analysis carried out on the data obtained is statistical and descriptive data analysis. The aspects studied in obtaining research puposes are community response variables, demographic variables, livelihood variables, norm variables, consumption pattern variables, and environmental variables. From the research results found that the percentage of changes that occur has a range of 1% to 50%. This shows that the tourism destination of The Lodge has no major effect on the socio-economic changes of the people. The results of this research can be used as a new learning resource for students in terms of social interaction. In addition, this research can be used by tourism destination managers in determining accommodative policies and Corporate Social Responsibility (CSR) programs will be created. While for the village government, the results of this research can be used as an indicator for reviewing the Memorandum of Understanding (MoU). In view of many other chapters of social science such as politics, culture, geology, and so on which can be used as new objects in further research on the same subject. Key Words : the socio-economic impacts, The Lodge tourism destination, and The people of Cibodas Village